Avaliação do impacto da hiperalgesia muscular crônica difusa na gestação e no neurodesenvolvimento da prole de ratas wistar - Oliveira, Ana Beatriz da Silva (2022)
Evaluation of the impact of widespread chronic muscle hyperalgesia on pregnancy and on the neurodevelopment of the offspring of wistar rats. Ana Beatriz da Silva Oliveira, São Cristóvão, SE, Brazil, 2022. Introduction: Fibromyalgia (FM) is one of the most common chronic musculoskeletal diseases, affecting mostly women and its etiology is still unknown.. It is suspected the involvement of environmental, autoimmune, hormonal or even genetic factors for its development. Because of this, there is concern about the impact of Fibromyalgia on the offspring of these women. The animal model of widespread chronic muscle hyperalgesia (WCMH) induced by acid saline, does not generate tissue damage and remains for up to 04 weeks, resembling fibromyalgia in humans. Hyperalgesia is a potent stressor and the fetal programming hypothesis states that adverse events occurring in the mother during pregnancy, such as chronic stress, imply changes in the health-disease pattern of her offspring. This study aimed to assess the impact of widespread chronic muscle hyperalgesia on pregnancy, as well as the response of neonatal reflexes and developmental milestones in the offspring. Methods: 18 rats were divided into three groups: 1- Acid saline (AS), 2- Neutral saline (NS) and 3- Control (CTRL). Initially WCMH was induced in the AS group, then scheduled mating of all groups followed. The mother rats were evaluated for behavior. The evaluation of the reflexes and developmental milestones of the offspring was performed by two independent evaluators, from postnatal day 01 to 21. Results: The hyperalgesia of the parent rats in the acid saline group showed a significant difference in the acid saline group with a reduction in the threshold after induction, showing that hyperalgesia was effective (p=0.0004). There was no hyperalgesia in the neutral and control groups, as expected (p=0.0846, p=0.5339, respectively). The results obtained demonstrate that WCMH does not prevent fertilization and copulation, the females of the acid saline group (AS) performed copulation on the first day of union with the male, showing a prosocial behavior and greater receptivity to the male than the males. neutral saline (NS) and Control (CTRL) groups. The gestation of the SA group lasted 22 days, while the NS and CTRL groups lasted 21 days. The AS group gave birth to 64 mice, the NS group gave birth to 42 mice, and the control group gave birth to 44 mice. The death of 8 pups was observed on the second postnatal day of the AS group. As for the reflexes, the offspring of the AS group presented a delay in the day of the appearance of the reflexes: palm grip, plantar grip, straightening, aversion to the precipice, auditory startle and straightening in free fall; when compared to the NS and CTRL groups. Conclusion: Our study demonstrates that hyperalgesia favors copulation and does not prevent pregnancy, but influences pregnancy leading to higher mortality in the offspring of the acidic saline group. An impact on six sensorimotor reflexes was observed in the AS group, showing a significant difference, indicating that hyperalgesia affected the fetal neurodevelopment of this offspring.